علاقة الفينيقيين بالجرامنت على الساحل الليبي خلال العصر الفينيقي (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:The study dealt with the nature of relationship of the Phoenicians Grament to the Libyan coast during the Phoenician era, where the Phoenicians settled on the Libyan coast after their exit from their country on the eastern coast of the Mediterranean basin as a result of many reasons, including political, economic, social and environmental reasons, and founded commercial stations for rest, water food, supplies and discharge their products during their frequent going and returning from the western Mediterranean to trade and search for the equipment required for their advanced industry during that period. The most important of these stations were Leptis Magna, Cyrene and Sabratha. The relationship between the three stations and the Gramant tribe was friendly and distinctive between the merchants, the Gramants and their Carthaginian counterparts. They were exchanging trade goods coming from the desert eyelids, and goods coming to the stations. Jarma became an important hub where products were collected for commercial caravans across the desert to the oceans, and several road caravan routes were found from the oceans to Jarma and from Jarma to the oceans. The commercial relationship between the two parties has ended, as North Africa became under Roman control as a result of several political, economic and social motives.
Keywords: Phoenicians; Gramants; Commercial goods; Land caravans; oceans